Everyone knows what you did: Evidence from public disclosure of COVID-19 and travel logs - Yoon, Chungeun (KDI School of Public Policy and Management, 2021)
I investigate the effect of public disclosure of detailed location information of people who tested positive for COVID-19 in Seoul. I use data on actual travel logs of people with COVID-19 where they visited before the quarantine, foot traffic from mobile phone signals, consumption spending from card transaction. I find that public disclosure decreased foot traffic and consumption spending for a week in exposure locations and did not increase new confirmed cases in the locations. The results suggest that public disclosure caused economic losses for a short term, but prevented the transmission of infection.